Kepuasan Pasien terhadap Pelayanan Kesehatan Gigi dan Mulut pada Praktik Kedokteran Gigi Mandiri di Kota Medan Tahun 2025 - Emerentia Angela; Susanna Halim; Alamsyah (Postgraduate, University of Mataram, 2025)
Patient satisfaction is a crucial indicator of healthcare service quality, particularly in dental and oral health services. This study aims to analyze the factors influencing patient satisfaction in an independent dental practice in Medan. A quantitative, descriptive-analytic approach was used, involving 50 patients who completed a structured questionnaire assessing various service dimensions, including timeliness, dentist competence, communication, and facility conditions. The findings indicate that dentist expertise had the highest impact on satisfaction, followed by responsiveness and communication. Statistical analysis revealed a significant correlation between service quality and patient satisfaction, with the strongest association found in professional expertise. Based on these results, recommendations include implementing a digital appointment system to optimize patient flow, providing continuous training for dentists on technical skills and patient interaction, and upgrading clinic facilities to improve patient comfort. Regular satisfaction surveys are also suggested for ongoing service evaluation and improvement. This study contributes by providing recent data in the post-pandemic dental care context in Medan.